Law Enforcement Against International Human Trafficking - Destina Rina Susanti; Rina Arum Prastyanti (International Journal of Law and Society, 2024)
International human trafficking is a serious crime that causes harm to millions of individuals in various parts of the world. The purpose of this article is to examine the challenges and prospects in law enforcement efforts against international human trafficking. Through an analytical approach, this research will investigate various aspects included in the relevant international legal framework, effective law enforcement strategies, as well as cooperative efforts between countries in handling human trafficking cases.